Identification and Ranking of Factors Affecting Innovation in Accounting - Mohammad Hossein Setayesh; Zahra Rezaeianzadeh (مطالعات تجربی حسابداری مالی, 2023)
The main goal of this research is to identify and rank factors affecting innovation in accounting. In this research, firstly, accounting specialists were selected by purposeful sampling methods, and then qualitative data were collected using open questionnaires. After analyzing the collected data using the phenomenology method, 11 factors were identified. Subsequently, a survey involving 17 faculty members from the accounting departments of Iranian public universities was conducted, and the Bayesian best-worst method was employed to rank these identified factors. Based on the results, the top 3 factors affecting innovation in accounting, in order of importance, include advances in information technology, changes in the business environment, and the level of financial knowledge and analytical skills of accountants. In order to improve the context of innovation in accounting, the results of this research suggest accountants should have general information about business and advances in information technology. They also, as the human capital of the innovation process in accounting, should continuously improve their level of financial knowledge and analytical skills.IntroductionIn recent years, the information technologies, such as cloud service models, big data, artificial intelligence, and blockchain are rapidly transforming the business environments and have raised concerns about the future of the accounting profession. Although these emerging technologies are still designed for the day-to-day work of accountants, they can significantly change the future work of accountants (Moll & Yigitbasioglu, 2019). It seems that in the face of the said technologies, the provision of accounting services, such as bookkeeping, preparing financial statements, preparing tax returns, and auditing, have all been subject to radical innovations (Bowles et al., 2020). According to the accounting literature, a new set of skills is necessary for accountants due to these emerging technologies. This is while job advertisements of Iranian companies (https://www.irantalent.com), still demand traditional job roles for accountants and instead, new job titles, such as fraud investigation specialist and senior data analyst have been emerging that can cover the newly defined job roles of accountants by literature. It seems that to reinforce the position of accountants in organizations, a change in accounting and in other words, the search for innovation in accounting is necessary.To address the lack of accounting literature in the field of innovation, the primary objective of this study is to identify and rank the factors that impact innovation in accounting by using qualitative methods, to initiate the expansion of innovative thinking and the creation of innovative ideas in accounting.MethodologyThis study used the phenomenology method to identify the factors affecting innovation in accounting. The accounting specialists were chosen as an informant using purposeful and snowball sampling methods. The twelve accounting specialists who participated in the research offered a wide range of services, including auditing, consulting, financial statement preparation, and tax accounting. Data collection was carried out mainly by means of an unstructured questionnaire supported by a telephone interview. Finally, by the use of Colaizzi’s method of data analysis, the factors affecting innovation in accounting were identified (Wirihana et al., 2018, p. 31).The Bayesian best-worst method was selected to rank the factors affecting innovation in accounting. The decision-makers were seventeen faculty members in the accounting department of Iranian public universities who had publications that transfer the concept of some sort of innovation in accounting. Bayesian best-worst method is based on pairwise comparison (Mohammadi & Rezaei, 2020). Pairwise comparison data from the decision-makers who participated in the research was collected through a standard questionnaire. Finally, using Python code for the chosen method, the factors affecting innovation in accounting were ranked.Results and DiscussionAccording to the results of Colaizzi’s method of data analysis, eleven factors were identified, and using the Bayesian best-worst method, the optimal weight of all factors was calculated. Table 1 presents the overall optimal weight and rank of factors affecting innovation in accounting. The findings indicate that the factors of advances in information technology (0.127806), changes in the business environment (0.12760311), and the level of financial knowledge and analytical skills of accountants (0.10951763) are respectively the most important factors. According to the optimal weight of all factors, it can be seen that none of the factors are irrelevant to innovation in accounting, because the weight of the least important factor is equal to 0.06665689. In fact, neither factor has an optimal weight lower than 0.065.ConclusionThe field of research into innovation in accounting is new, therefore this research generates new insight into the area. Among the practical implications, the study suggests that accountants consider environmental factors, such as advances in information technology and constantly update their knowledge and skills. It also suggests that they should improve their overall business knowledge by familiarizing themselves with different companies' operations and financial processes. Moreover, it suggests that they develop their analytical skills to be able to clarify the implications of decision-making results. Lastly, this study suggests that to achieve innovation in accounting, the conduct of research related to innovation and the cooperation of accountants can generate ideas to improve innovation in accounting.The study was qualitative in nature, as a result, this study cannot argue that the nature of innovation in accounting and the factors affecting it remain unchanged over time. Therefore, this study recommends more research in this field to contribute to a better understanding of innovation in accounting.